2015
DOI: 10.1111/1471-0528.13456
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and network meta‐analysis comparing the use of Foley catheters, misoprostol, and dinoprostone for cervical ripening in the induction of labour

Abstract: Background Various methods are used for cervical ripening during the induction of labour. It is still debatable which of these methods of treatment is optimal.Objective To compare treatment techniques for cervical ripening in the induction of labour.Search strategy Medline, Embase, and the Cochrane Collaboration databases were searched using the keywords 'cervical ripening', 'labour induced', 'misoprostol', 'dinoprostone', and 'Foley catheter'.Selection criteria Randomised controlled trials (RCTs) of cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
138
4
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 24 publications
3
138
4
7
Order By: Relevance
“…5 A retrospective study that included cases with PROM emphasized that no difference was found in neonatal outcome between two PG E2 forms (gel and vaginal insert form). Also, it was reported that there was no statistical difference in terms of operative vaginal delivery between two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 A retrospective study that included cases with PROM emphasized that no difference was found in neonatal outcome between two PG E2 forms (gel and vaginal insert form). Also, it was reported that there was no statistical difference in terms of operative vaginal delivery between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 In the absence of any contraindication to vaginal delivery, active management can be carried out by induction of labor via using pharmacological or nonpharmacological methods. 5,6 Oxytocin is the most common pharmacological agent used traditionally for induction of labor in women with PROM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is more effective than amniotomy with intravenous oxytocin which can result in increased caesarean delivery, especially if the cervix is 'not ripe' [6][7][8][9]. Doses ranging from 20-200µg, with frequencies varying from hourly to six hourly and the administration of up to 12 doses of 50 µg over four days have been reported.…”
Section: Low Dose Oral Misoprostolmentioning
confidence: 99%
“…Doses ranging from 20-200µg, with frequencies varying from hourly to six hourly and the administration of up to 12 doses of 50 µg over four days have been reported. A starting dose of 20 µg of oral misoprostol in solution, titrated against uterine contractions and administered hourly in increasing doses of up to 60 µg, is currently thought to be a safe, cost effective method for induction of labour [6][7][8][9][10]. The hourly dosing regimen has been calculated according to the pharmacokinetics of oral misoprostol.…”
Section: Low Dose Oral Misoprostolmentioning
confidence: 99%